Psychological distress and its associated factors in health workers during COVID-19 pandemic in Nepal: An online survey - Nirmala Shrestha; Nisha Gurung; Sanju Banstola; Saurabh Kishor Sah; Sharad Koirala; Bimala Sharma (Journal of Gandaki Medical College, 2021)
Introduction: Psychological distress among healthcare workers amidst COVID-19 pandemic has emerged as a serious health problem. Understanding its magnitude is crucial to guide policies and interventions to improve their psychological wellbeing. This study assessed the psychological distress and its associated factors among health care workers in Nepal during the COVID-19 pandemic.